2020
DOI: 10.7150/ijbs.40823
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses inflammation and apoptosis of myocardiocytes by inhibiting autophagy in a model of ischemia-reperfusion injury

Abstract: Metformin (Met) is a major widely used oral glucose lowering drug for the treatment of type 2 diabetes. It is reported that metformin could regulate autophagy in various diseases of cardiovascular system including in I/R injury, diabetic cardiomyopathy and heart failure. Autophagy plays a controversial role in ischemia/reperfusion (I/R) injury, and this research was performed to explore the cardioprotective effect of Met on I/R injury and discuss the underlying mechanism of autophagy in it. In vivo and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
(76 reference statements)
2
16
0
Order By: Relevance
“…In our study, we observed that PF11 increased the levels of anti-oxidative stress related proteins SOD1, HO1, and eNOS in the random skin flaps implying that PF11 has anti-oxidative stress effects. Reperfusion triggers the overproduction of ROS which may lead to mitochondrial dysfunction and apoptosis ( Daverey and Agrawal, 2020 ; Huang et al, 2020 ). Inhibition of apoptosis effectively prevents cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that PF11 increased the levels of anti-oxidative stress related proteins SOD1, HO1, and eNOS in the random skin flaps implying that PF11 has anti-oxidative stress effects. Reperfusion triggers the overproduction of ROS which may lead to mitochondrial dysfunction and apoptosis ( Daverey and Agrawal, 2020 ; Huang et al, 2020 ). Inhibition of apoptosis effectively prevents cell death.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be linked to a protective effect on heart muscle cells from being damaged and dying (Fei et al 2020. However, there is also contradicting evidence that rather implicates a downregulation of autophagy through activation of the Akt signalling pathway as protective metformin effects; different results may be related to differences in methodology, for example, administering metformin prior to ischaemia or during reperfusion (Huang et al 2020). Another key result of AMPK activation by metformin seems to be inhibition of toll-like receptor 4 (TLR4), leading to significantly lower levels of proinflammatory cytokines and attenuation of left ventricular dysfunction in mouse models of myocardial infarction (Soraya et al 2012, Vaez et al 2016.…”
Section: Heartmentioning
confidence: 99%
“…Treatment with metformin significantly attenuates I/R induced pathological changes and cellular apoptosis in mouse hearts. The inhibition of autophagosome formation and restoration of the impaired autophagosome processing contributes to metformin's cardioprotective effect, dependent on the Akt signaling pathway (Huang et al, 2020). BALB/c mice exposed to LPS challenge have an elevation of creatinine kinase-myocardial band (CK-MB) and brain natriuretic peptide (BNP) in plasma.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%